Integrated Nanostructural Electrodes Based on Layered Double Hydroxides. Issue 3 (22nd June 2019) - Xie, Wenfu; Song, Yuke; Li, Shijin; Shao, Mingfei; Wei, Min
Abstract : Layered double hydroxides (LDHs), as a class of typical two‐dimensional materials, have sparked increasing interest in the field of energy storage and conversion. In the last few years, the research about LDHs as electrode active materials has seen much progress in terms of structure designing, material synthesis, properties tailoring, and applications. In this review, we focus on the integrated nanostructural electrodes (INEs) construction using LDH materials, including pristine LDH‐INEs, hybrid LDH‐INEs, and LDH derivative‐INEs, as well as the performance advantages and applications of LDH‐INEs. Moreover, in the final section, the insights about challenges and prospective in this promising research field were concluded, especially in regulation of intrinsic activity and uncovering of structure–activity relationship, which would push forward the development of this fast‐growing field. Abstract : Recent progress in integrated nanostructural electrodes (INEs) construction using layered double hydroxides (LDHs)‐based materials is summarized and highlighted. Some personal insights about the challenges and prospective in this promising research field are concluded, which is expected to push forward the development of this fast‐growing field.